HIV/AIDS in Georgia : Addressing the Crisis - Gotsadze, Tamar; Chawla, Mukesh; Chkatarashvili, Ketevan (Washington, DC: World Bank, 2013)
Georgia is experiencing fast growing HIV/AIDS epidemic, although the prevalence remains at low level. The primary mode of transmission are injecting drug users representing 71 percent of cases, followed by 22 percent heterosexual contacts, 3.6 percent homo-bisexual contacts, 1.4 percent blood recipients, 1 percent of vertical transmission. From 1989 to 1998 the epidemic progressed slowly with sporadic occurrences. However, even at this low level of transmission, the infection had reached all administrative regions of the country. Since 1996 the situation has changed dramatically. The number of HIV cases increased nearly three fold in 1997 compared with the previous year and accounted for 21 cases. In 2001 alone, this number reached 93. From 1998 through 2001 more than half of newly-registered HIV infection cases have been attributed to IDUs. The reports indicate that the percentage of new cases attributed to heterosexual contacts have also increased, although the absolute numbers remain small. More people (mostly women) appear to be contracting HIV through sexual transmission, suggesting a shift of the epidemic into the general population. HIV/AIDS is predominantly present in the age group of 21-35 years, while children between the ages of 5 and 15 provide a special opportunity and window of hope. In 2001, over 87 percent of all new AIDS cases are detected in the individuals of 26-35 years age group. As this is the most economically productive segment of the population, deaths in this age group cause great economic hardship to the families. Many productive years and investment in education and training is thus lost. These deaths also have significant family consequences, since most people in this age are raising young children. During the last three years three cases of HIV infection have been detected among pregnant women, and two cases of vertical transmission have been reported, thus sexual mode of transmission becomes apparent. The situation is further complicated with the transfusion of non-screened blood in case of emergencies becoming a common practice due to the failure of adequate public financing on the one hand, while the number of infected blood donors is increasing on the other.